A Novel Rat Model to Test Intra-Abdominal Anti-adhesive Therapy - Vediappan, Rajan Sundaresan; Bennett, Catherine; Bassiouni, Ahmed; Smith, Matthew; Finnie, John; Trochsler, Markus; Psaltis, Alkis J.; Vreugde, Sarah; Wormald, Peter J. (Frontiers in Surgery, 2020)
Background: Adhesion formation after abdominal surgery is considered almost inevitable and a major cause of morbidity. Novel treatments have been proposed, however there is a lack of suitable small animal models for pre-clinical evaluation, mainly due to inconsistency in adhesion formation in positive control animals. Here, we propose a new rat model of abdominal adhesions using Kaolin as the adhesion-inducing agent at an optimised dosage for testing newer agents in respect to their anti-adhesive property. Materials and Methods: Twenty-five adult (8-10 week old) male Wistar albino rats underwent midline laparotomy and caecal abrasion and were randomized to receive topical applications of normal saline or different concentrations and volumes of a Kaolin-based formulation. At day 14 rats were humanely killed, and adhesions graded macroscopically by an investigator blinded to the treatment groups, using pre-determined adhesion scores and microscopically using histopathology. Results: Kaolin at 0.005 g/mL caused consistent adhesions without compromising rat viability. At higher doses significant morbidity and mortality was observed in the animals treated. Conclusions: Kaolin induced adhesion in a rat abdominal surgery model is reliable and can be safely used to test the efficacy of novel anti-adhesive formulations to prevent intra-abdominal adhesions.